2022
DOI: 10.12968/jowc.2022.31.9.771
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of diabetic foot ulcers: review of the literature with regard to the TIME clinical decision support tool

Abstract: Objective: The aim of this clinically orientated paper is to offer an overview of diabetic foot ulcer (DFU) dressings generally, and more specifically, their use in the treatment of DFUs. Method: The TIME clinical decision support tool (CDST) has been used as a clinical tool that can help clinicians bring together the different aspects of dressings for DFU treatment into a holistic approach to patient care. Results: DFUs are often difficult to heal, are painful and impact negatively on the individual's quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Bigger, more homogeneous samples are mandatory for this examination. This was also emphasised in previous studies that employed a related meta‐analysis technique and found equivalent results of the effect 23‐27 …”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Bigger, more homogeneous samples are mandatory for this examination. This was also emphasised in previous studies that employed a related meta‐analysis technique and found equivalent results of the effect 23‐27 …”
Section: Discussionmentioning
confidence: 72%
“…Honey has an acidic pH range of 3.2 to 4.5. Additionally, an acidic environment might speed up haemoglobin's release of oxygen, which would benefit wound healing 23‐27 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Debridement is a process for removing non-viable and necrotic tissue. That is, the removal of callus, necrotic tissue and bacterial components at the wound by surgery, hydrogel, biosurgery (i.e., maggots), to promote the release of growth factors and accelerate the transformation of chronic wounds into acute wounds [ 12 , 13 ]. In addition, decompression can be achieved by debridement of the healing tissue.…”
Section: Introductionmentioning
confidence: 99%